Proteomic analysis of a candida albicans pga1 null strain - Awad, Andy (2018)
We previously characterized Pga1, a Candida albicans (C. albicans) cell wall protein necessary for proper virulence, adhesion, and resistance to oxidative stress. By utilizing tandem mass spectrometry coupled with bioinformatics to investigate cell wall proteome expression in a pga1 null fourteen and 36 proteins were identified in the wild type grown under filamentous and non-filamentous conditions respectively, but were not detected in the mutant, including members of the PGA GPI anchored family. Virulence and adhesion proteins such as Hsp 90, Sap10, Cdc11, Int 3 and members of the lipase family were also identified exclusively in the wild type.